Effect of maturational timing on bone health in male adolescent athletes engaged in different sports: The PRO-BONE study. Issue 3 (March 2019) - Ubago-Guisado, Esther; Vlachopoulos, Dimitris; Barker, Alan R.; Christoffersen, Tore; Metcalf, Brad; Gracia-Marco, Luis
Abstract: Objectives: To describe differences in bone outcomes according to biological age in male athletes participating in osteogenic (OS) or non-osteogenic (NOS) sports. Design: Longitudinal (12-months). Methods: 104 adolescents (12–14 years) were measured at baseline and after 1y: OS group (n = 37 football or soccer players) and NOS group (n = 39 swimmers, n = 28 cyclists). Years from peak height velocity (PHV, −2 to +2) was used as a maturational landmark. Bone mineral content (BMC) was assessed using DXA. Hip structural analysis estimated cross-sectional area (CSA), cross-sectional moment of inertia (CSMI) and section modulus (Z) at the femoral neck (FN). Trabecular bone score (TBS) estimated lumbar spine (LS) texture. Quantitative ultrasound measured bone stiffness. Multilevel regression models adjusted by hours of training were fitted. Results: Compared to NOS, OS had significantly greater total body (less head) BMC from PHV to +2 years from PHV (from 9.5% to 11.3%, respectively); LS BMC from −1 years from PHV to PHV (from 9.8% to 9.9%); hip BMC (from 11.6% to 22.9%), FN BMC (from 12.0% to 15.9%), TBS (from 4.2% to 4.8%) and stiffness index (from 11.9% to 23.3%) from −1 years from PHV to +2 years from PHV; and CSA (from 8.4% to 18.8%), Z (from 5.5% to 22.9%) and CSMI (from 10.6% to 23.3%) from −2 years from PHV to +2 years from PHV. There was a significant trend for the between-group differences to increase with biological age except for LS BMC and TBS. Conclusions: These findings underline the differential bone response to different sports throughout the years surrounding PHV in male adolescent athletes. Clinical trial registration: ISRCTN17982776.